PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V SD NEGERI 168 PEKANBARU - Rusmina Manurung; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve learning outcomes math class V students of SD Negeri 168 Pekanbaru with the application of Learning Model Discovery Learning. Problems that affect student learning outcomes Low is a) The process of learning is teacher center teacher means they are more active or dominant, b) Model of Learning lectures which in the model teachers do not encourage students to find their own. The subjects were all students of class V SD Negeri 168 Pekanbaru, with the number of 35 students, with details of 15 male students and 20 female students. Object in the research is to increase the student’s mathematics learning outcomes outcomes through Application Discovery Learning Learning Model class V SD Negeri 168 Pekanbaru. This research is two cycles, the each cycle consisting of two meetings and test. Improved student learning completeness average percentage of student learning outcomes through the first cycle was 71.4%, in the second cycle reached a percentage of average value of 88.6%, while the base score is only 57.1%. The average student learning outcomes has increased from a base score to the first cycle as much as 6.58%, in the second cycle the average student learning outcomes increased by 15.41%. Basically the student’s learning outcomes can be demonstrated that through the implementation of Learning Model Discovery Learning mathematics can improve learning outcomes Student Class V SD Negeri 168 Pekanbaru.Keywords: Discovery Learning Model, Mathematic Learning Outcomes